Determination of gonad maturation stages morphologically and the reproduction period in Sillago suezensis (Forsskal, 1775) (Sillaginidae) migratory from the Red Sea in the marine waters of Latakia Governorate - بسيمه زين العابدين; وعد صابور; أمينة النسر (Latakia University Journal -Biological Sciences Series, 2024)
This research was carried out on /338/ individuals of fish Sillago suezensis from the migratory in Syrian coast, during the period between 23/6/2022 and 23/6/2023, different means used locally private fishing nets, especially the gill nets, at depths ranging from 3 m to 50 m. The TL (total length) of the samples varies between (10 -20.6) cm with an average TL is (15.01± 2.1) cm for females and (8-20.3) cm with an average TL is (15.07± 1.97) for males. The TW (total weight) of the specimens ranges between (5.84-69.98) g with an average value of (27.77 ±11.55) g for females and (2.84 ±67.71) g with an average value of (27.15 ±10.55) g for males. The duration of reproduction was determined by studying the GSI%. The GSI% was highest in June (4.58 ± 2) for males and in September (6.22 ± 2.77) for females. The breeding season for this species extends from May to November. The stages of development of gonad maturity conformed morphologically corresponded to the six-sided scale of gonad maturity.